Kepuasan keluarga terhadap Perawatan di Unit Rawatan Rapi (icu), Hospital Universiti Sains Malaysia - Ali Aminuddin, Moho Rasani (PPSP, Universiti Sains Malaysia, 2007)
Background:· Study on patient's family satisfaction with care at the ICU, HUSM was done due to the inability to communicate directly with the critical patients. Family members could not communicate with patients as they are not allowed to stay with patients at the ICU. Increased awareness among the public about the importance of health care has made the hospital and health care providers involved directly to provide the best quality health care. The health care quality depends on customer's or patient's satisfaction of the care that they were provided. However, customers' satisfaction was not only measured from the patients themselves but also from the family members of the patients. Objective:- To know the family satisfaction level of care of patient treated at the ICU and their role as decision maker for patient and to identify the demographic factors associated with family satisfaction level. Methodology: - Sixty four patients' family members were selected as respondents. They were the family members of the patients who were treated at the ICU from the period of December 2006 to January 2007. Questionnaires were used to measure their satisfaction level. Results: -The results of this study shown that majority of the respondents were satisfied and only a few were not satisfied. Overall, this was levelled as good.There were significant difference (p<0.05) for both of the satisfaction with patient care and satisfaction with the role of decision maker for patient care. Family members' age, marital status and the frequency of visiting were also significantly (p<0.05) associated with family satisfaction of patient care. Conclusion: - Family satisfaction level was still considered as good at ICU, HUSM. Majority of respondents in this study were categorized as satisfied. Least was categorized as not satisfied.